The Lived experience of Iranian Mothers in the role of Mother-in-law: A phenomenological Study - Montazeri, Roya (Applied Family Therapy Journal (AFTJ), 2023)
Objective: The aim of the present study was to identify the lived experiences of Iranian mothers from the role of mother-in-law. Research Method: The method of the present study was applied and qualitative descriptive phenomenology. The sample consisted of 14 mothers living in Isfahan who entered the study by convenience sampling method. Semi structured interviews were conducted, then implemented verbatim and analyzed by the Smith and Osborn’s method. Results:In this study, The role of mother-in-law in 4 main themes including the perception of motherhood after marriage, role-playing requirements, challenges and opportunities, communication skills, 15 sub-themes including supportive and guiding motherhood, conservative motherhood, motherhood Self-sacrificing with personal limitations, desirable traits and characteristics, challenges and opportunities of relationship with spouse, challenges and opportunities of parent-child relationship, challenge of cultural beliefs, an opportunity to respond to basic needs, challenge Care and management responsibilities, emotional challenges, maintaining boundaries, expressive and instrumental investment, joining the family of spouse child, joining the in-law, acting consciously and intelligently, and were estimated 69 codes. Conclusion: According to the research findings, the role of mother-in-law is defined by the perception of a supportive, conservative and self-sacrificing mother, who is required to have desirable characteristics and traits and use communication skills to fulfill her role. Being a mother-in-law, while creating opportunities, also brings challenges for mothers. In general, facilitating relationships and family cohesion is the common essence of Iranian mothers’ experiences the role of mother-in-law.